Social media, personal branding, and the hypoesthesia of communication corruption - Bambang Sukma Wijaya; Asri Annisa Nasution (Cogent Arts & Humanities, 2022)
The increasing use and misuse of social media in personal branding have prompted the recent study to examine it from the perspective of communication corruption, namely the act of reducing the audience’s right to receive messages completely and correctly according to facts. This study uses a phenomenological approach by interviewing in-depth key informants from academics who have personal branding experience through social media. We found some communication corruption in the dimensions of the message (such as in visual touch-ups and exaggerating facts), media (abusing media utilities and manipulating media features), context (constructing fake situations and settings to create desired impressions), and behavior (deliberately manipulating and deceiving). The informants admitted to doing this because it is normal and common for netizens in the social media world. We call this phenomenon hypoesthesia of communication corruption, namely the banality of the immorality in interpreting corrupt actions and events in communication. This study is the first in the issue of communication corruption in personal branding through social media and the first to present the concept of hypoesthesia of communication corruption based on empirical insights.